Peningkatan Hasil Belajar Biologi dengan Model Discovery Learning - Sri Gening Sundari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The research aim was to find out the improvement of biology achievement of the tenth grade students of science class at SMA Negeri 3 Lubuklinggau. The research method used was Classroom Action Research. The population was all of the tenth grade students of science class. The sampling technique was purposive sampling technique with 32 students as the samples. The instruments of data collection were observation sheets and tests. The data were analyzed both through quantitative and qualitative descriptive method. The results showed that the students achievement was improved indicated by initial percentage 37%, cycle I 43,75 % to 59,37 % in cycle II. The data of students learning activities were collected from some parameters such as students' activities, response, cooperation, responsibilities, tolerances, and diligence with the average score in cycle I only 62,03 and it was improved in cycle II to 79,53. In conclusion, discovery learning model could improve students' learning achievements and students' learning activities. Keywords: students achievement, model discovery learning